2006
DOI: 10.2174/092986706775476070
|View full text |Cite
|
Sign up to set email alerts
|

Agonists and Antagonists of Protease Activated Receptors (PARs)

Abstract: Protease activated receptors (PARs) are a category of G-protein coupled receptors (GPCRs) implicated in the progression of a wide range of diseases, including thrombosis, inflammatory disorders, and proliferative diseases. Signal transduction via PARs proceeds via an unusual activation mechanism. Instead of being activated through direct interaction with an extracellular signal like most GPCRs, they are self-activated following cleavage of their extracellular N-terminus by serine proteases to generate a new re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 141 publications
1
76
0
Order By: Relevance
“…Thus, further experiments dealing with, for example, purified primary cultured human osteoblasts, are needed. Recent developments indicate that TF, when bound to FVIIa, is involved in cell signaling, especially through PAR-2 activation [2]. In this paper, we showed that, in an osteoblastic-like cell line, TF is expressed and acts as a signaling factor.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Thus, further experiments dealing with, for example, purified primary cultured human osteoblasts, are needed. Recent developments indicate that TF, when bound to FVIIa, is involved in cell signaling, especially through PAR-2 activation [2]. In this paper, we showed that, in an osteoblastic-like cell line, TF is expressed and acts as a signaling factor.…”
Section: Discussionmentioning
confidence: 69%
“…Thrombin digests fibrinogen into fibrin monomers [1]. TF is expressed in non-circulating and circulating cells [2], as well as organs [3]. Recently, an alternatively spliced tissue factor (asTF), consisting only of the extracellular sequence, was identified in humans and mice [4].…”
Section: Introductionmentioning
confidence: 99%
“…16 Compound 1 is unstable in vivo due to proteolysis, but the non-peptidic agonist 2 is a promising template for elaborating to a plasma stable PAR2 antagonist. We previously reported that replacement of the C-terminal primary amine in 2 with a morpholine group produced a weak antagonist (3,IC 50 Structure-activity relationship (SAR) studies on the PAR2 antagonist GB88 (4) suggested that the isoxazolyl, cyclohexyl-alanine and isoleucine residues were intolerant of other substitution for antagonist potency (unpublished results). Our PAR2 homology model (derived from ORL-1 receptor crystal structure 4EA3)…”
Section: Graphical Abstractmentioning
confidence: 97%
“…[1][2][3][4] PAR2 is expressed in immune and inflammatory cells including T-cells, monocytes, macrophages as well as in many types of cancer cells. [3][4][5][6] There has been some controversy about PAR2 activation being pro-and/or anti-inflammatory.…”
Section: Graphical Abstractmentioning
confidence: 99%
See 1 more Smart Citation